Annexin A2 Regulates Phagocytosis of Photoreceptor Outer Segments in the Mouse Retina - Law, Ah-Lai (The American Society for Cell Biology, 2009)
The daily phagocytosis of shed photoreceptor outer segments by pigment epithelial cells is critical for the maintenance of the retina. In a subtractive polymerase chain reaction analysis, we found that functional differentiation of human ARPE19 retinal pigment epithelial (RPE) cells is accompanied by up-regulation of annexin (anx) A2, a major Src substrate and regulator of membrane–cytoskeleton dynamics. Here, we show that anx A2 is recruited to the nascent phagocytic cup in vitro and in vivo and that it fully dissociates once the phagosome is internalized. In ARPE19 cells depleted of anx A2 by using small interfering RNA and in ANX A2(−/−) mice the phagocytosis of outer segments was impaired, and in ANX A2(−/−) mice there was an accumulation of phagocytosed outer segments in the RPE apical processes, indicative of retarded phagosome transport. We show that anx A2 is tyrosine phosphorylated at the onset of phagocytosis and that the synchronized activation of focal adhesion kinase and c-Src is abnormal in ANX A2(−/−) mice. These findings reveal that anx A2 is involved in the circadian regulation of outer segment phagocytosis, and they provide new insight into the protein machinery that regulates phagocytic function in RPE cells.